Identifikasi Penggunaan Obat Off Label pada Pasien Geriatri dengan Penyakit Degeneratif di Puskesmas Sugio - Berliana Putri Nabella; Irma Susanti; Devi Ristian Octavia (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2026)
Prescribing medications that do not comply with the official information stated on the drug label and marketing authorization, such as dose, age, route of administration, contraindications, and indications, is known as off-label drug use. Elderly patients may experience undesirable adverse effects due to off-label medication use. This study aimed to evaluate off-label drug use among elderly individuals with degenerative diseases at Sugio Primary Health Center. This study collected data retrospectively from the medical records of elderly patients with degenerative disorders at Sugio Primary Health Center using a descriptive non-experimental design. The sample was selected using a purposive sampling method. The inclusion criteria were geriatric patients aged ≥60 years diagnosed with degenerative diseases who received outpatient care during the period of January–August 2024. Data were collected using an observation sheet and analyzed using univariate analysis. The findings from 150 patients showed that 69 (46%) were categorized as off-label dose and 58 (38.7%) as off-label age. These findings indicate that off-label drug use still occurs among elderly patients, highlighting the need to evaluate the rationality of prescribing practices.